Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 7 - Section 7.1 - Radical Expressions and Graphs - 7.1 Exercises - Page 440: 38



Work Step by Step

We know that $\sqrt[3] -64=-4$, because $(-4)^{3}=-4\times-4\times-4=-64$. Therefore, $-\sqrt[3] -64=-(-4)=4$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.